Global Patterns of Father Absence: A Systematic Literature Review of Causes - Lira Erwinda; Laura Viqueira Gutiérrez; Ndirangu Ngunjiri; Paseka Kholopane; Jayvee Escoton (Asosiasi Asesmen Pendidikan (AAP), 2025)
The global phenomenon of father absence significantly affects children's psychological, academic, and social development. This study employs a Systematic Literature Review (SLR) approach to pinpoint and consolidate the patterns and causes of father absence worldwide. We searched four primary databases Scopus, Web of Science, ERIC, Google Scholar and found 253 articles. Following a screening process based on the PRISMA inclusion and exclusion criteria, we selected ten articles for detailed analysis. The synthesis reveals that factors such as labor migration, marital conflict, patriarchal cultural standards, and unsupportive social policies contribute to father absence. The impacts include children's reduced emotional well-being, lower academic achievement, and poorer social adjustment. These results support the idea that father absence is a multifaceted issue influenced not just by individual factors but also by structural and cultural elements. As such, inclusive policies and societal changes that promote fathers' emotional engagement and equal parenting duties are essential.